Respostas
respondido por:
1
f(0)= 1/2.0 (-6) = 1/-6 = -1/6
f(1) = 1/2.1 - 6 = 1/ 2 - 6 = 1/ -4 = -1/4
f(2)= 1/ 2.2 -6 = 1/4-6 = 1/-2 = -1/2
f(-1) = 1/2(-1)-6 = 1/-2-6 = 1/-8 = -1/8
f(-2) = 1/2(-2)-6 = 1/-4-6 = 1/-10 = -1/10
f(1) = 1/2.1 - 6 = 1/ 2 - 6 = 1/ -4 = -1/4
f(2)= 1/ 2.2 -6 = 1/4-6 = 1/-2 = -1/2
f(-1) = 1/2(-1)-6 = 1/-2-6 = 1/-8 = -1/8
f(-2) = 1/2(-2)-6 = 1/-4-6 = 1/-10 = -1/10
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás